Annex 2: Study of uncertainty for quality assessment of loss data - Xavier Romão (2014)
This report presents a state of the art for recording disaster loss data in European Union member states. It summarizes the contribution of experts from 15 EU Member States. A comparative analysis shows that methodologies for disaster loss data collection and recording in Europe are heterogeneous and that the available loss databases vary in their level of completeness and detail. Also IT systems vary in purpose, complexity and openness. This precludes a reliable and representative aggregation of loss data at the EU level. This report provides recommendations to European Union Member States that would help increase the quality of (shared) loss data within the current policy framework. It is recommended to continue the consultative process in a third phase with the aim of expanding the network of Member States ready to participate, tackling remaining technical issues in the EU framework for disaster loss recording and assisting Member States in implementing better loss data recording processes.